A Farewell to Arms : The Challenge of Studying Politics by Former Rebels in Colombia (2009)
This paper is a result of an investigation that was carried out by the Interdisciplinary Research Center (CIES) of the Faculty of Law and Social Sciences of Icesi University in Cali, Colombia, as a part of a broader project under the auspices of the United Nations Development Program (UNDP) in Colombia, to study the cases of best practices to overcome the conflict. These cases have been organized in a public database, which is maintained by UNDP3 .